Invasive non-typhoidal Salmonella (iNTS) aminoglycoside-resistant ST313 isolates feature unique pathogenic mechanisms to reach the bloodstream - Martins, Isabela Mancini [UNESP]; Seribelli, Amanda Aparecida; Machado Ribeiro, Tamara R. [UNESP]; da Silva, Patrick [UNESP]; Lustri, Bruna Cardinali [UNESP]; Hernandes, Rodrigo T. [UNESP]; Falcão, Juliana Pfrimer; Moreira, Cristiano Gallina [UNESP] (Elsevier, 2023)
Invasive non-typhoidal Salmonella (iNTS) from the clonal type ST313 (S. Typhimurium ST313) is the primary cause of invasive salmonellosis in Africa. Recently, in Brazil, iNTS ST313 strains have been isolated from different sources, but there is a lack of understanding of the mechanisms behind how these gut bacteria can break the gut barrier and reach the patient's bloodstream. Here, we compare 13 strains of S. Typhimurium ST313, previously unreported isolates, from human blood cultures, investigating aspects of virulence and mechanisms of resistance. Initially, RNAseq analyses between ST13-blood isolate and SL1344 (ST19) prototype revealed 15 upregulated genes directly related to cellular invasion and replication, such as sopD2, sifB, and pipB. Limited information is available about S. Typhimurium ST313 pathogenesis and epidemiology, especially related to the global distribution of strains. Herein, the correlation of strains isolated from different sources in Brazil was employed to compare clinical and non-clinical isolates, a total of 22 genomes were studied by single nucleotide polymorphism (SNPs). The epidemiological analysis of 22 genomes of S. Typhimurium ST313 strains grouped them into three distinct clusters (A, B, and C) by SNP analysis, where cluster A comprised five, group B six, and group C 11. The 13 clinical blood isolates were all resistant to streptomycin, 92.3% of strains were resistant to ampicillin and 15.39% were resistant to kanamycin. The resistance genes acrA, acrB, mdtK, emrB, emrR, mdsA, and mdsB related to the production of efflux pumps were detected in all (100%) strains studied, similar to pathogenic traits investigated. In conclusion, we evidenced that S. Typhimurium ST313 strains isolated in Brazil have unique epidemiology. The elevated frequencies of virulence genes such as sseJ, sopD2, and pipB are a major concern in these Brazilian isolates, showing a higher pathogenic potential.
Keywords: Galleria mellonella; Phylogeny; RNA-seq; Salmonella Typhimurium ST313; Virulence and resistance genes